توسيع وتضييق المعنى في القرآن الكري: Expanding and Narrowing the Meaning in the Holy Qur’an - Muhammad Quwwatul Islam Abdurrahman (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
This study aims to identify semantic developments in the pronunciation of the Qur'an based on modern linguistic studies, and to find out the views of linguists and commentators both classical and contemporary, regarding the manifestations of semantic development, especially in narrowing and expanding the meaning contained in pronunciation. -recitation of the Qur'an, and knowledge of linguistic phenomena and their factors. This study uses a descriptive analytical approach. The results show that classical and contemporary scholars have clarified the pronunciations in the Qur'an which refer to a broader meaning than in the past, and the connotations are wider than before, and show a narrower meaning than before, and its connotations become narrower than before.